Aplikasi Pembelajaran Interaktif Sistem Kardiovaskular - Andre Timothy Kapugu; Brave A. Sugiarso; Steven R. Sentinuwo (Jurnal Teknik Elektro dan Komputer, 2023)
Abstract — In the learning process students need to combine new knowledge with knowledge that has been previously learned, making students build an integrated understanding between previous knowledge, new knowledge and other relevant knowledge. Inappropriate learning methods, teacher-dominated learning, and a lack of teaching aids or teaching aids make students tend to have difficulty connecting what is being taught to them with other concepts. This allows students to experience misconceptions. Misconceptions become an obstacle for students in increasing learning understanding and have a negative impact if left unchecked which makes the level of students' understanding of the material low. The purpose of this study is to create interactive learning applications that help high school students improve their understanding of the cardiovascular system. Making an Android-based cardiovascular system interactive learning application using the Multimedia Development Life Cycle development method. The test results showed that of the 30 students of XI IPA SMA there was an increase in correct answers by 29% from the pretest average score of 48% before using the application and the post-test average score of 77% after using the application. As many as 93.3% of students are interested in using the application and the remaining 6.7% of students are less interested in using the application. This application provides learning and attracts students to use the application.   Key words— Cardiovascular System; Interactive; Learning; Multimedia Development Life Cycle.   Abstrak — Dalam proses pembelajaran siswa perlu memadukan pengetahuan baru dengan pengetahuan yang telah dipelajari sebelumnya, membuat siswa membangun pemahaman terpadu antara pengetahuan sebelumnya, pengetahuan baru dan pengetahuan lain yang relevan. Metode pembelajaran yang kurang tepat, pembelajaran yang didominasi oleh guru, serta kurangnya sarana atau alat peraga membuat siswa cenderung mengalami kesulitan menghubungkan apa yang diajarkan kepada mereka dengan konsep lainnya. Hal ini memungkinkan siswa mengalami miskonsepsi. Miskonsepsi menjadi penghambat siswa dalam peningkatan pemahaman pembelajaran dan berdampak negatif apabila dibiarkan yang membuat tingkat pemahaman siswa terhadap materi menjadi rendah. Tujuan dari penelitian ini untuk membuat aplikasi pembelajaran interaktif yang membantu siswa SMA dalam meningkatkan pemahaman materi sistem kardiovaskular. Pembuatan aplikasi pembelajaran interaktif sistem kardiovaskular berbasis android menggunakan metode pengembangan Multimedia Development Life Cycle. Hasil pengujian menunjukan bahwa dari 30 siswa XI IPA SMA terdapat peningkatan jawaban benar sebanyak 29% dari nilai ratarata pretest 48% sebelum menggunakan aplikasi dan nilai rata-rata post-test 77% setelah menggunakan aplikasi. Sebanyak 93,3% siswa tertarik menggunakan aplikasi dan sisa     6,7% siswa kurang tertarik menggunakan aplikasi. Aplikasi ini memberikan pembelajaran dan menarik siswa untuk menggunakan aplikasi.   Kata kunci — Interaktif; Multimedia Development Life Cycle; Pembelajaran; Sistem Kardiovaskular.